The Faculty of Medicine of the University of Maribor Celebrates 20 Years : Medicinska fakulteta Univerze v Mariboru je dopolnila 20 let - Takač, Iztok (Acta Medico-Biotechnica, 2023)
The Faculty of Medicine of the University of Maribor (MF UM) was established on October 2nd, 2003. The Council of the Republic of Slovenia for Higher Education ratified the university study programme “General Medicine” on December 3rd, 2003, whereupon in autumn 2004, the first 89 students enrolled in this programme. Since then, and until the end of the year 2023, 1,090 students will have completed their studies with a degree. The Council of the Republic of Slovenia for Higher Education gave consent, with an agreement, to the implementation of the new doctoral study programme “Biomedical Technology” at the MF UM on April 15th, 2005. In the academic year 2005/06, the first generation of postgraduate doctoral students was enrolled, specifically, 29 students in the first and 16 students in the second study year. From then, and until the end of 2023, there will have been 156 Doctors of Science promoted at the MF UM. The Slovenian Quality Assurance Agency for Higher Education bestowed the accreditation of the UMSP “Dental Medicine” programme on the MF UM on January 9th, 2020. The first generation of 20 students of “Dental Medicine” enrolled in the academic year 2021/22. In the beginning, the MF UM operated in numerous locations. On April 30th, 2004, the renewed building at Ljubljanska Ulica 5 was handed over for use, and on January 27th, 2006, the building at Magdalena Trg 5 followed. The foundation stone for the new building at Taborska Ulica 8 was laid on June 20th, 2011. The construction lasted for two years and three months, whereupon it was handed over for use on September 18th, 2013. The MF UM includes 36 university departments and 11 institutes. Professional services are organized into three departments: the Student and Study Affairs and the International Cooperation Department, the Economic and General Affairs Department and the Legal and General Affairs Department.
Keywords: the Faculty of Medicine, the University of Maribor, anniversary, 20 years, medical studies